Penguatan Kesejahteraan Masyarakat melalui Pengelolaan Dana Bantuan UMKM: Tinjauan Ekonomi Islam - Riana Putri, Septi; Ligery, Finny; Agus Mushodiq, M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Management of aid funds for the MSME group is an important strategy in improving community welfare, especially in areas with a lower middle economic level. In an Islamic economic perspective, the management of these funds must refer to the principles of justice (al-adl), sustainability (istidama), benefit (maslahah), and be free from elements of usury, gharar and maisir. This research aims to analyze the effectiveness of managing MSME aid funds in improving community welfare based on sharia principles. The results of the analysis show that sharia-based approaches, such as channeling funds through qard al-hasan (interest-free loans), mudharabah (profit sharing) or productive waqf schemes, can increase business sustainability and empower MSMEs. In addition, implementing transparency, financial education and business assistance are key factors in ensuring funds are used productively. Targeted management of funds also contributes to increasing income, creating jobs and strengthening social solidarity in society. However, there are several challenges such as inaccurate targets, misuse of funds, and a lack of understanding by MSME actors regarding sharia financial principles. To overcome this, an integrated management strategy is needed, involving sharia financial institutions, and the use of digital technology to monitor the allocation and use of funds in real-time.